Respostas fisiológicas da tilápia-do-nilo e variáveis limnológicas após decomposição de macrófitas utilizando herbicida - Nomura, Daniela Takahashi; Meneses, Juliana Oliveira; Pilarski, Fabiana [UNESP]; de Moraes, Flavio Ruas [UNESP]; Abe, Higo Andrade; Fujimoto, Rodrigo Yudi (Boletim do Instituto de Pesca, 2017)
Macrophytes are important for aquatic biocenosis, however under certain conditions it’s population can raise becoming a problem in reservoirs such as the Egeria densa. To control these plants CONAMA discuss for the use of chemicals, but feasibility and safety studies should be conducted to allow the use for such purpose. Thus the present study evaluated the effects of decomposition Egeria densa killed by the herbicide diquat on water quality variables and physiological responses of Nile tilapia. Thus, 176 tilapia was distributed in 16 tanks and submitted to four treatments (tilapia without macrophyte; tilapia and macrophyte; tilapia and macrophytes died by diquat and macrophytes died by freezing). The values of pH, temperature, dissolved oxygen, alkalinity and conductivity did not differ between treatments. However, it observed an increase in total ammonia and phosphorus and reduction of nitrite concentrations in treatment with macrophyte killed by the herbicide. Chlorophyll-a concentration did not differ between treatments, however, phaeophytin-a increased in water submitted to plants died by freezing. After 21 days of experiment, no differences were observed in blood glucose, cortisol, leukocytes, erythrocytes and hemoglobin. Thus, tilapia does not alter their physiological patterns after chronic exposure to decomposing macrophytes killed by diquat.
Physiological responses of nile tilapia and water parameters after decomposition of macrophyte using herbicide
Keywords: Aquatic plants; Cronic stress; Environmental impact; Oreochromis niloticus